Hydrogeochemical and geophysical investigations to delineate underground water aquifer in arid regions: A case study, Gara oasis, Egypt - NAZIH, Mohamed; GOBASHY, Mohamed Mostafa; SALEM, Zenhom; SOLIMAN, Khaled Soliman; HASSAN, Ahmed AbdelHalim M. (Contributions to Geophysics and Geodesy, 2022)
The goal of the present study is to investigate, delineate, and evaluate the shallow Miocene groundwater aquifer with vertical and lateral facies variations in the Gara oasis, western desert of Egypt. This oasis represents a typical arid region in North Africa. Through grid texture analysis, lineament detection, edge detection, thresholding, and identifying areas of structural complexity from the filtered residual reduced-to-pole magnetic anomaly map, it is possible to outline the fracture zones that principally control the groundwater aquifers and water flow in the area. The groundwater quality and quantity are examined hydro-geochemically through nine groundwater samples that were gathered from wells and springs distributed throughout the area around Gara Lake. Measurements of physio-chemical parameters (TDS, pH, and EC) are carried out and its spatial distribution is critically studied. The results reveal that the ion-exchange process caused by water-rock interaction is the dominant process. Furthermore, the main ions in the groundwater in the study areas were Na and Cl. This might be due to evaporation or halite dissolution with the upward flow of waters through the fractures from the deep aquifer of the Nubian sandstone to the shallow aquifer of the fractured Miocene limestone.